PENGARUH PEMBERIAN BIOURINE DAN PUPUK KALIUM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Eka Saputra; Nelvia Nelvia; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The efforts of increasing growth, development and productivity of red onionthrough fertilization. Organic and inorganic fertilizers are used. This combination of fertilizers is expected to increase the growth of shallots, because the functions as a nutrient source and it is able to improve the physical and biological properties of the land.The study was conducted on the experimental field of the Agriculture Faculty University of Riau on February until April 2018. A randomized block design with two factors are used in this study. The first factor was 4 levels of biourine (control, 200 ml.l-1, 250ml.l-1, and 300 ml.l-1).The second factor was 4 levels of potassium(control, 36kg K2O.ha-1, 54kgK2O.ha-1, and 72kgK2O.ha-1). The parameters that were observed such as leaf length, number of leaves, number of tubers, tubers, fresh weight of tubers per clump, fresh weight of tubers per plot, tuber weight worth keeping. The result showed that there were interaction between biourin and potassium on fresh weight parameters per plot and fresh weight worth keeping per plot. The main factor treatment of biourin has significant effect through all of parameters that were observed. The main factor treatment of potassium fertilizer has a significant effect through all of observational parameters except on the parameters of the number of tubers.The combination of good treatment were obtained from the treatment of biourin and potassium at a concentration of 250 ml.l-1 at a dose of 72 kg K2O.ha-1. Keywords:Biourin, Potassium, Red Onion (Allium ascalonicum L.